ANALISIS BIAYA PENGOBATAN HIPERTENSI PADA PASIEN RAWAT INAP DI RSD dr. SOEBANDI JEMBER PERIODE JANUARI 2011-NOVEMBER 2012 - Marlina, Ni Ketut; Rina Herowati; Tri Murti Andayani (Jurnal Ilmiah Kesmas -IJ, 2019)
Hypertension is a medical condition in which there is an increase in systolic blood pressure of 140 mmHg or a diastolic pressure of 90 mm ​​Hg at rest. Research purposes to determine patterns of treatment of hypertension, the average cost of treatment, the factors that affect the total cost, and the cost of compliance with the real cost of the package INA-CBGs on patient health card. The study was an observational cross-sectional study design according to the perspective of the hospital. Method of data collection was done in retrosfektif and data derived from quantitative data. Subjects were inpatients suffering from hypertension without comorbidities / strage II hypertension and hypertension with comorbid diabetes mellitus, heart failure and kidney failure. Data were analyzed descriptively to determine the characteristics of patients and the average cost of treatment. Bivariate Ujikorelasi to determine the factors that significantly affect the cost of treatment of hypertension and test one sample t-test to determine the total cost of compliance with health costs based on INA-CBGs. The results showed an average total cost of hypertensive patients for general patients and the health card row is Rp. 1,950,000 and Rp. 2.33 million. Effect of length of stay and the severity value P = 0.000 and P = 0.005 is a factor any significant difference to the total cost of treatment of hypertension. Suitability for a total cost of strage II hypertension, hypertensive heart failure +, DM + hypertension, renal failure and hypertension + row Rp. 1,900,000, Rp. 2,900,000, Rp. 3,750,000, Rp. 2.18 million with health financing by INA-CBG Rp. 2,903,555.55, Rp. 5,262,984.61, Rp. 4,629,555.55, and Rp. 3,960,977.95 showed a significant difference with a P> 0.05